Preparation method and application of fluorine-doped and carbon-coated synergistically modified lithium-rich manganese-based single-crystal positive electrode material based on PVDF (Polyvinylidene Fluoride)
Through the coordinated modification method of fluorine doping and carbon coating of PVDF, the problem of poor structural stability of lithium-rich manganese-based positive electrode materials during charging and discharging is solved, and efficient electrochemical cycle stability and feasibility of large-scale production is achieved.
Patent Information
- Application Number
- CN202510638276.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-19
- Publication Date
- 2025-08-26
AI Technical Summary
Most of the existing lithium-rich manganese-based positive electrode materials are polycrystalline structures, and microcracks are prone to occur during charging and discharging, resulting in structural collapse and electrolyte penetration, resulting in capacity attenuation. In addition, traditional preparation methods are difficult to meet the GWh-level capacity requirements.
The precursor is prepared by co-precipitation reaction by co-precipitation reaction, and the solid-phase doping sintering of PVDF is carried out after oxidation treatment, and the particle size is controlled by airflow grinding to prepare a lithium-rich manganese-based single crystal positive electrode material with both fluorine doping and carbon coating.
It significantly improves the electronic conductivity and lattice stability of the material, inhibits side reactions, extends battery life, and reduces the degree of cation mixed discharge, making it suitable for large-scale industrial production.
Smart Images

Figure CN120535029A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and specifically to a preparation method and application of a lithium-rich manganese-based single crystal positive electrode material modified by fluorine doping and carbon coating based on PVDF. Background Art
[0002] As the core technology for next-generation energy storage systems, lithium-ion batteries are driving technological advancements in electric vehicles and smart grids. Among numerous cathode material systems, lithium-rich manganese-based materials (xLi2MnO3·(1-x)LiMO2) are considered key to achieving 400Wh / kg-class high-energy-density batteries due to their breakthrough theoretical specific capacity (>300mAh / g), high operating voltage platform, and the cost advantages of manganese-based materials.
[0003] At present, the mainstream lithium-rich manganese-based positive electrode materials on the market are mostly polycrystalline structures. Due to the anisotropy of polycrystalline material particles, microcracks are easily generated on the surface of the material during the charge and discharge cycle, which in turn causes structural collapse and cracking in subsequent cycles, accelerates electrolyte penetration, and triggers irreversible phase change (layered → spinel / rock salt phase) and transition metal dissolution, resulting in capacity decay. In contrast, single crystal structures, with their lower internal stress and larger specific surface area, can provide more active sites, effectively inhibit the generation of microcracks during the cycle, and significantly improve the cycle life and specific capacity of the material. From the perspective of single crystal preparation methods, although the hydrothermal method and sol-gel method can achieve single crystal morphology control, it is difficult to meet GWh-level production capacity requirements in terms of cost and yield. Summary of the Invention
[0004] In order to overcome the shortcomings of the above-mentioned prior art, the present invention innovatively proposes a preparation method for a lithium-rich manganese-based single crystal positive electrode material by synergistic modification of fluorine doping and carbon coating based on PVDF. The method starts with the preparation of a precursor by co-precipitation reaction. After oxidation treatment, PVDF solid-phase doping and sintering are used to cleverly achieve uniform incorporation of fluorine elements and in-situ coating of a carbon layer. Subsequently, the particle size is precisely controlled by air flow milling, and finally a lithium-rich manganese-based single crystal positive electrode material Li with both carbon coating and fluorine doping is successfully prepared. 1.2 Ni x Mn y O 2-x F x @C.
[0005] In the present invention, the fluorine element is released from PVDF and enters the material lattice, which can effectively adjust the electronic structure of the material, significantly enhance the lattice stability, and effectively prevent the loss of lattice oxygen; and the carbon coating formed by the pyrolysis of PVDF can greatly improve the electronic conductivity of the material, while effectively blocking the side reactions between the electrolyte and the active substance, curbing the occurrence of side reactions from the source. In addition, the innovative preparation process adopted by the present invention greatly improves the distribution uniformity of the ions of each component, significantly reduces the degree of cation mixing, and avoids the use of expensive organic reagents. It has the significant advantages of simple process and easy cost control, which meets the actual needs of large-scale industrial production and opens up a new path for the research and development of high-energy-density lithium-ion battery positive electrode materials.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] A method for preparing a lithium-rich manganese-based single crystal positive electrode material by synergistic modification of fluorine doping and carbon coating based on PVDF comprises the following steps:
[0008] S1. Solution preparation: Prepare a transition metal salt solution at a molar ratio of Ni:Mn=1:(2.2-3), and simultaneously prepare a NaOH aqueous solution and an NH3·H2O aqueous solution;
[0009] S2. Precursor preparation: The transition metal salt solution, NaOH aqueous solution and NH3·H2O aqueous solution are slowly pumped into a reactor containing NH3·H2O and deionized water at the same time, and the pH value of the reaction is controlled to be maintained at 11-11.2. After the reaction is completed, [Ni x Mn y ](OH)2 precursor, wherein 0.25≤x≤0.3125,0.6875≤y≤0.75, the [Ni x Mn y The particle size of the ](OH)2 precursor is 2-5 μm;
[0010] S3, precursor pre-oxidation: the [Ni x Mn y ](OH)2 precursor is pre-sintered in a pure oxygen atmosphere;
[0011] S4, the pre-sintered [Ni x Mn y The precursor of ](OH)2 is mixed with PVDF and lithium source, and then calcined twice in nitrogen atmosphere to obtain a lithium-rich manganese-based polycrystalline cathode material Li with loose secondary particles and both fluorine doping and carbon coating modification. 1.2 Ni x Mn y O 2-z F z@C, where 0.20≤x≤0.25,0.55≤y≤0.60,0≤z≤0.1;
[0012] S5, crushing the lithium-rich manganese-based polycrystalline positive electrode material under a jet mill to obtain a lithium-rich manganese-based single crystal positive electrode material Li with both fluorine doping and carbon coating modification. 1.2 Ni x Mn y O 2-z F z @C.
[0013] Preferably, the transition metal salt solution in step S1 contains Ni 2+ and Mn 2+ The total concentration is 2-4 mol L -1 ; The concentration of the NaOH aqueous solution is 2-4 mol L -1 The concentration of the NH3·H2O aqueous solution is 1-2 mol L -1 .
[0014] Preferably, the transition metal salt in step S1 is selected from one of sulfate, chloride and nitrate, and the sulfate is NiSO4·6H2O and MnSO4·H2O.
[0015] Preferably, during the preparation of the small-particle precursor in step S2, the reaction temperature is controlled at 50-55° C., and stirring is performed continuously in an inert protective gas atmosphere at a stirring rate of 700-900 rpm.
[0016] Preferably, the pre-sintering temperature in step S3 is 400-500° C., and the pre-sintering time is 300-360 min.
[0017] Preferably, the lithium source in step S4 is selected from at least one of LiOH·H2O, LiNO3, and Li2CO3; the pre-sintered [Ni x Mn y ]The molar ratio of the (OH)2 precursor to the lithium source is 1:(1.50-1.60).
[0018] Preferably, the secondary calcination in step S4 is specifically as follows: heating to 500-600°C at a heating rate of 2°C / min-5°C / min in an oxygen atmosphere, keeping warm for 6-8 hours for sintering; then heating to 910-950°C, keeping warm for 10-15 hours for solid phase lithium insertion reaction.
[0019] Preferably, the amount of PVDF added is 0-5 mol % based on the total amount of anionic substances.
[0020] The present invention also provides an application of PVDF-based fluorine-doped and carbon-coated synergistically modified lithium-rich manganese-based single crystal positive electrode material, and the prepared positive electrode material is coated with a slurry made of a conductive agent, a binder and a solvent to produce a positive electrode sheet.
[0021] Preferably, the prepared positive electrode plate is used for the preparation of a lithium-ion battery, and when preparing a lithium-ion battery, the active material on the negative electrode plate is selected from one or more of graphite, artificial graphite, silicon-carbon material, lithium metal negative electrode and lithium-carbon negative electrode material.
[0022] Compared with the prior art, the beneficial effects of the present invention are: utilizing PVDF to release fluorine elements for doping during the sintering process, and simultaneously forming a carbon-based coating layer, effectively overcoming the problems of uneven doping and insufficient interface stability existing in traditional simple doping or coating processes. By rationally controlling the amount of PVDF used and the sintering conditions, uniform doping of fluorine elements in the crystal lattice and in-situ continuous coating of the carbon layer are achieved, and the prepared lithium-rich manganese-based single crystal material has the characteristics of excellent crystallinity, interface stability, and uniform composition. This material not only significantly improves the electrochemical cycle stability and rate performance, but also further extends the service life of the battery by suppressing structural phase changes and side reactions. The process flow of the present invention is simple, the preparation efficiency is high, it is easy to promote and apply on a large scale, and it has broad industrialization prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 [Ni prepared in Example 1 0.25 Mn y0.55 ]SEM image of (OH)2 precursor;
[0024] Figure 2 The lithium-rich manganese-based single crystal cathode material Li prepared in Example 1 based on PVDF collaborative doping and coating modification 1.2 Ni 0.25 Mn 0.55 O 1.95 F 0.05 @SEM image of C;
[0025] Figure 3 The lithium-rich manganese-based single crystal cathode material Li prepared in Example 1 based on PVDF collaborative doping and coating modification 1.2 Ni 0.25 Mn 0.55 O 1.95 F 0.05 @C's SEM corresponding energy spectrum;
[0026] Figure 4 The lithium-rich manganese-based single crystal positive electrode material Li prepared based on different PVDF addition amounts in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 9 of the present invention is 1.2 Ni 0.25 Mn0.55 O 2-x F x XRD pattern of @C;
[0027] Figure 5 The lithium-rich manganese-based single crystal positive electrode material Li prepared based on different PVDF addition amounts prepared in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 9 of the present invention 1.2 Ni 0.25 Mn 0.55 O 2-x F x @C The first cycle charge and discharge curve of the assembled battery at 0.1C (1C = 210mA / g);
[0028] Figure 6 The lithium-rich manganese-based single crystal positive electrode material Li prepared based on different PVDF addition amounts prepared in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 9 of the present invention 1.2 Ni 0.25 Mn 0.55 O 2-x F x @C Cycling performance curve of the battery assembled at a current density of 0.5C. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0030] Example 1
[0031] S1. Solution preparation: Prepare transition metal salt solution containing NiSO4·6H2O and MnSO4·H2O. 2+ 、Mn 2+ The molar ratio of Ni is 1:2.2. 2+ 、Mn 2+ The sum of the concentrations is 2 mol / L, and 4 mol / L NaOH solution and 1 mol / L ammonia water are prepared.
[0032] S2. Preparation of precursor: Under a high-purity nitrogen atmosphere, a 2 mol / L transition metal salt solution was injected into the reactor at a constant rate of 0.3 L / h. At the same time, 1 mol / L ammonia water was added as a complexing agent, and 4 mol / L NaOH solution was added as an alkaline solution. By precisely adjusting the flow rate of the NaOH solution, the pH value of the reaction system was controlled between 11.0 and 11.1 to prepare [Ni 0.3125 Mn 0.6875](OH)2 precursor. The stirring speed of the reactor was kept at 900 rpm and the reaction temperature was 50°C. During the reaction, as the precursor continued to grow, the particle size analysis of the reaction product was performed every hour. When the particle size D 50 When the particle size reaches 3-4 microns, the reaction is terminated, and the reaction product is then aged in the reactor for 12 hours. After the aging is completed, the precursor is washed, filtered, and finally dried to obtain [Ni 0.3125 Mn 0.6875 ](OH)2 precursor.
[0033] S3, Precursor pre-oxidation: The obtained [Ni 0.3125 Mn 0.6875 ](OH)2 precursor was heated in pure oxygen atmosphere at 3℃min -1 The temperature was raised to 500℃ at a heating rate and kept at this temperature for 300min for pre-oxidation.
[0034] S4, PVDF double modification: the pre-oxidized [Ni 0.3125 Mn 0.6875 The precursor of ](OH)2 was mixed with PVDF (HSV900, doping amount was 2.5 mol%) and LiOH·H2O (TM:Li molar ratio = 1:1.55) and heated at 3 °C min in nitrogen atmosphere. -1 Heat to 500℃ and keep it for 400min, then heat it at 2℃min -1 The temperature was raised to 930℃ and kept for 13h to obtain a lithium-rich manganese-based polycrystalline cathode material Li with loose secondary particles and both fluorine doping and carbon coating modification. 1.2 Ni 0.25 Mn 0.55 O 1.95 F 0.05 @C.
[0035] S5. Preparation of single crystal: crushing the lithium-rich manganese-based polycrystalline positive electrode material in a jet mill to obtain a lithium-rich manganese-based single crystal positive electrode material Li with both fluorine doping and carbon coating modification. 1.2 Ni 0.25 Mn 0.55 O 1.95 F 0.05 @C,D 50 =0.45μm, D 90 =0.60um.
[0036] A positive electrode plate is prepared by coating a slurry made of a lithium-rich manganese-based single crystal positive electrode material that is both fluorine-doped and carbon-coated, a conductive agent, a binder and a solvent.
[0037] A lithium-ion battery comprising the positive electrode sheet and the negative electrode sheet;
[0038] The active material on the negative electrode plate is selected from one or more of graphite, artificial graphite, silicon-carbon material, lithium metal negative electrode and lithium-carbon negative electrode material.
[0039] Example 2
[0040] S1. Solution preparation: Prepare transition metal salt solution containing NiSO4·6H2O and MnSO4·H2O. 2+ 、Mn 2+ The molar ratio of Ni is 1:3. 2+ 、Mn 2+ The sum of the concentrations is 3 mol / L, and 3 mol / L NaOH solution and 2 mol / L ammonia water are prepared.
[0041] S2. Preparation of precursor: Under a high-purity nitrogen atmosphere, a 3 mol / L transition metal salt solution was injected into the reactor at a constant rate of 0.3 L / h. At the same time, 2 mol / L ammonia water was added as a complexing agent and 3 mol / L NaOH solution was added as an alkaline solution. By precisely adjusting the flow rate of the NaOH solution, the pH value of the reaction system was controlled between 11.1 and 11.2 to prepare [Ni 0.25 Mn 0.75 ](OH)2 precursor. The stirring speed of the reactor was kept at 850 rpm and the reaction temperature was 55°C. During the reaction, as the precursor continued to grow, the particle size analysis of the reaction product was performed every hour. When the particle size D 50 When the particle size reaches 3-4 microns, the reaction is terminated, and the reaction product is then aged in the reactor for 12 hours. After the aging is completed, the precursor is washed, filtered, and finally dried to obtain [Ni 0.25 Mn 0.75 ](OH)2 precursor.
[0042] S3, Precursor pre-oxidation: The obtained [Ni 0.25 Mn 0.75 ](OH)2 precursor was heated in pure oxygen atmosphere at 3℃min -1 The temperature was raised to 450°C at a heating rate of 10000 ℃ and kept at this temperature for 300 minutes for pre-oxidation.
[0043] S4, PVDF double modification: the pre-oxidized [Ni 0.25 Mn 0.75 The precursor of ](OH)2 was mixed with PVDF (HSV900, doping amount was 1.5 mol%) and LiOH·H2O (TM:Li molar ratio = 1:1.55) and heated at 2 °C min in nitrogen atmosphere. -1 Heat to 600℃ and keep it for 400min, then heat it at 2℃min-1 The temperature was raised to 930℃ and kept for 15h to obtain a lithium-rich manganese-based polycrystalline cathode material Li with loose secondary particles and both fluorine doping and carbon coating modification. 1.2 Ni 0.2 Mn 0.6 O 1.97 F 0.03 @C.
[0044] S5. Preparation of single crystal: crushing the lithium-rich manganese-based polycrystalline positive electrode material in a jet mill to obtain a lithium-rich manganese-based single crystal positive electrode material Li with both fluorine doping and carbon coating modification. 1.2 Ni 0.2 Mn 0.6 O 1.97 F 0.03 @C,D 50 =0.35μm, D 90 =0.55μm.
[0045] A positive electrode plate is prepared by coating a slurry made of a lithium-rich manganese-based single crystal positive electrode material that is both fluorine-doped and carbon-coated, a conductive agent, a binder and a solvent.
[0046] A lithium-ion battery comprising the positive electrode sheet and the negative electrode sheet;
[0047] The active material on the negative electrode plate is selected from one or more of graphite, artificial graphite, silicon-carbon material, lithium metal negative electrode and lithium-carbon negative electrode material.
[0048] Example 3
[0049] S1. Solution preparation: Prepare transition metal salt solution containing NiSO4·6H2O and MnSO4·H2O. 2+ 、Mn 2+ The molar ratio of Ni is 1:2.4, 2+ 、Mn 2+ The sum of the concentrations is 2 mol / L, and 2 mol / L NaOH solution and 1 mol / L ammonia water are prepared.
[0050] S2. Preparation of precursor: Under a high-purity nitrogen atmosphere, a 3 mol / L transition metal salt solution was injected into the reactor at a constant rate of 0.3 L / h. At the same time, 1 mol / L ammonia water was added as a complexing agent, and 2 mol / L NaOH solution was added as an alkaline solution. By precisely adjusting the flow rate of the NaOH solution, the pH value of the reaction system was controlled between 11.1 and 11.2 to prepare [Ni 0.295 Mn 0.705](OH)2 precursor. The stirring speed of the reactor was maintained at 900 rpm and the reaction temperature was 55°C. During the reaction, as the precursor continued to grow, the particle size analysis of the reaction product was performed every hour. When the particle size D 50 When the particle size reaches 3-4 microns, the reaction is terminated, and the reaction product is then aged in the reactor for 12 hours. After the aging is completed, the precursor is washed, filtered, and finally dried to obtain [Ni 0.295 Mn 0.705 ](OH)2 precursor.
[0051] S3, Precursor pre-oxidation: The obtained [Ni 0.295 Mn 0.705 ](OH)2 precursor was heated in pure oxygen atmosphere at 3℃min -1 The temperature was raised to 500°C at a heating rate of 1000 °C and kept at this temperature for 300 min for pre-oxidation.
[0052] S4, PVDF double modification: the pre-oxidized [Ni 0.295 Mn 0.705 The precursor of ](OH)2 was mixed with PVDF (HSV900, doping amount was 3.5 mol%) and Li2CO3 (TM:Li = 1:1.55 molar ratio) and heated at 3 °C min in nitrogen atmosphere. -1 Heat to 500℃ and keep it for 400min, then heat it at 3℃min -1 The temperature was raised to 920℃ and kept for 12h to obtain a lithium-rich manganese-based polycrystalline cathode material Li with loose secondary particles and fluorine doping and carbon coating modification. 1.2 Ni 0.235 Mn 0.565 O 1.93 F 0.07 @C.
[0053] S5. Preparation of single crystal: crushing the lithium-rich manganese-based polycrystalline positive electrode material in a jet mill to obtain a lithium-rich manganese-based single crystal positive electrode material Li with both fluorine doping and carbon coating modification. 1.2 Ni 0.235 Mn 0.565 O 1.93 F 0.07 @C,D 50 =0.40μm, D 90 =0.65μm.
[0054] A positive electrode plate is prepared by coating a slurry made of a lithium-rich manganese-based single crystal positive electrode material that is both fluorine-doped and carbon-coated, a conductive agent, a binder and a solvent.
[0055] A lithium-ion battery comprising the positive electrode sheet and the negative electrode sheet;
[0056] The active material on the negative electrode plate is selected from one or more of graphite, artificial graphite, silicon-carbon material, lithium metal negative electrode and lithium-carbon negative electrode material.
[0057] Example 4
[0058] S1. Solution preparation: Prepare transition metal salt solution containing NiSO4·6H2O and MnSO4·H2O. 2+ 、Mn 2+ The molar ratio of Ni is 1:2.8, 2+ 、Mn 2+ The sum of the concentrations is 2 mol / L, and 4 mol / L NaOH solution and 2 mol / L ammonia water are prepared.
[0059] S2. Preparation of precursor: Under a high-purity nitrogen atmosphere, a 2 mol / L transition metal salt solution was injected into the reactor at a constant rate of 0.3 L / h. At the same time, 2 mol / L ammonia water was added as a complexing agent and 4 mol / L NaOH solution was added as an alkaline solution. By precisely adjusting the flow rate of the NaOH solution, the pH value of the reaction system was controlled between 11.1 and 11.2 to prepare [Ni 0.263 Mn 0.737 ](OH)2 precursor. The stirring speed of the reactor was kept at 900 rpm and the reaction temperature was 50°C. During the reaction, as the precursor continued to grow, the particle size analysis of the reaction product was performed every hour. When the particle size D 50 When the particle size reaches 3-4 microns, the reaction is terminated, and the reaction product is then aged in the reactor for 12 hours. After the aging is completed, the precursor is washed, filtered, and finally dried to obtain [Ni 0.263 Mn 0.737 ](OH)2 precursor.
[0060] S3, Precursor pre-oxidation: The obtained [Ni 0.263 Mn 0.737 ](OH)2 precursor was heated in pure oxygen atmosphere at 3℃min -1 The temperature was raised to 500°C at a heating rate of 1000 °C and kept at this temperature for 300 min for pre-oxidation.
[0061] S4, PVDF double modification: the pre-oxidized [Ni 0.263 Mn 0.737 The precursor of ](OH)2 was mixed with PVDF (HSV900, doping amount was 5 mol%) and Li2CO3 (TM:Li = 1:1.55 molar ratio) and heated at 2 °C min in nitrogen atmosphere. -1 Heat to 500℃ and keep warm for 300min, then heat at 3℃min -1The temperature was raised to 910℃ and kept for 14h to obtain a lithium-rich manganese-based polycrystalline cathode material Li with loose secondary particles and both fluorine doping and carbon coating modification. 1.2 Ni 0.21 Mn 0.59 O 1.90 F 0.1 @C.
[0062] S5. Preparation of single crystal: crushing the lithium-rich manganese-based polycrystalline positive electrode material in a jet mill to obtain a lithium-rich manganese-based single crystal positive electrode material Li with both fluorine doping and carbon coating modification. 1.2 Ni 0.21 Mn 0.59 O 1.90 F 0.1 @C,D 50 =0.35μm, D 90 =0.55μm.
[0063] A positive electrode plate is prepared by coating a slurry made of a lithium-rich manganese-based single crystal positive electrode material that is both fluorine-doped and carbon-coated, a conductive agent, a binder and a solvent.
[0064] A lithium-ion battery comprising the positive electrode sheet and the negative electrode sheet;
[0065] The active material on the negative electrode plate is selected from one or more of graphite, artificial graphite, silicon-carbon material, lithium metal negative electrode and lithium-carbon negative electrode material.
[0066] Example 5
[0067] S1. Solution preparation: Prepare transition metal salt solution containing NiSO4·6H2O and MnSO4·H2O. 2+ 、Mn 2+ The molar ratio of Ni is 1:2.2. 2+ 、Mn 2+ The sum of the concentrations is 2 mol / L, and 3 mol / L NaOH solution and 1 mol / L ammonia water are prepared.
[0068] S2. Preparation of precursor: Under a high-purity nitrogen atmosphere, a 2 mol / L transition metal salt solution was injected into the reactor at a constant rate of 0.3 L / h. At the same time, 1 mol / L ammonia water was added as a complexing agent, and 3 mol / L NaOH solution was added as an alkaline solution. By precisely adjusting the flow rate of the NaOH solution, the pH value of the reaction system was controlled between 11.1 and 11.2 to prepare [Ni 0.3125 Mn 0.6875](OH)2 precursor. The stirring speed of the reactor was kept at 850 rpm and the reaction temperature was 50°C. During the reaction, as the precursor continued to grow, the particle size analysis of the reaction product was performed every hour. When the particle size D 50 When the particle size reaches 3-4 microns, the reaction is terminated, and the reaction product is then aged in the reactor for 12 hours. After the aging is completed, the precursor is washed, filtered, and finally dried to obtain [Ni 0.3125 Mn 0.6875 ](OH)2 precursor.
[0069] S3, Precursor pre-oxidation: The obtained [Ni 0.3125 Mn 0.6875 ](OH)2 precursor was heated in pure oxygen atmosphere at 3℃min -1 The temperature was raised to 500°C at a heating rate of 1000 °C and kept at this temperature for 300 min for pre-oxidation.
[0070] S4, PVDF double modification: the pre-oxidized [Ni 0.3125 Mn 0.6875 The precursor of ](OH)2 was mixed with PVDF (HSV2850, doping amount was 2.5 mol%) and LiOH·H2O (TM:Li = 1:1.55 molar ratio) and heated at 3 °C min in nitrogen atmosphere. -1 Heat to 500℃ and keep it for 400min, then heat it at 2℃min -1 The temperature was raised to 930 ° C and kept for 13 hours to obtain a lithium-rich manganese-based polycrystalline cathode material Li with loose secondary particles and both fluorine doping and carbon coating modification. 1.2 Ni 0.25 Mn 0.55 O 1.95 F 0.05 @C.
[0071] S5. Preparation of single crystal: crushing the lithium-rich manganese-based polycrystalline positive electrode material in a jet mill to obtain a lithium-rich manganese-based single crystal positive electrode material Li with both fluorine doping and carbon coating modification. 1.2 Ni 0.25 Mn 0.55 O 1.95 F 0.05 @C,D 50 =0.45μm, D 90 =0.60um.
[0072] A positive electrode plate is prepared by coating a slurry made of a lithium-rich manganese-based single crystal positive electrode material that is both fluorine-doped and carbon-coated, a conductive agent, a binder and a solvent.
[0073] A lithium-ion battery comprising the positive electrode sheet and the negative electrode sheet;
[0074] The active material on the negative electrode plate is selected from one or more of graphite, artificial graphite, silicon-carbon material, lithium metal negative electrode and lithium-carbon negative electrode material.
[0075] Comparative Example 1
[0076] S1. Solution preparation: Prepare transition metal salt solution containing NiSO4·6H2O and MnSO4·H2O. 2+ 、Mn 2+ The molar ratio of Ni is 1:2.2. 2+ 、Mn 2+ The sum of the concentrations is 2 mol / L, and 4 mol / L NaOH solution and 1 mol / L ammonia water are prepared.
[0077] S2. Preparation of precursor: Under a high-purity nitrogen atmosphere, a 2 mol / L transition metal salt solution was injected into the reactor at a constant rate of 0.3 L / h. At the same time, 1 mol / L ammonia water was added as a complexing agent, and 4 mol / L NaOH solution was added as an alkaline solution. By precisely adjusting the flow rate of the NaOH solution, the pH value of the reaction system was controlled between 11.0 and 11.1 to prepare [Ni 0.3125 Mn 0.6875 ](OH)2 precursor. The stirring speed of the reactor was kept at 900 rpm and the reaction temperature was 50°C. During the reaction, as the precursor continued to grow, the particle size analysis of the reaction product was performed every hour. When the particle size D 50 When the particle size reaches 3-4 microns, the reaction is terminated, and the reaction product is then aged in the reactor for 12 hours. After the aging is completed, the precursor is washed, filtered, and finally dried to obtain [Ni 0.3125 Mn 0.6875 ](OH)2 precursor.
[0078] S3, Precursor pre-oxidation: The obtained [Ni 0.3125 Mn 0.6875 ](OH)2 precursor was heated in pure oxygen atmosphere at 3℃min -1 The temperature was raised to 500°C at a heating rate of 1000 °C and kept at this temperature for 300 min for pre-oxidation.
[0079] S4, PVDF double modification: the pre-oxidized [Ni 0.3125 Mn 0.6875 The precursor of ](OH)2 was mixed with PVDF (HSV900, doping amount was 3.5 mol%) and LiOH·H2O (TM:Li molar ratio = 1:1.55) and heated in nitrogen atmosphere at 3℃min -1 Heat to 500℃ and keep it for 400min, then heat it at 2℃min-1 The temperature was raised to 930 ° C and kept for 13 hours to obtain a lithium-rich manganese-based polycrystalline cathode material Li with loose secondary particles and both fluorine doping and carbon coating modification. 1.2 Ni 0.25 Mn 0.55 O 1.93 F 0.07 @C.
[0080] S5. Preparation of single crystal: crushing the lithium-rich manganese-based polycrystalline positive electrode material in a jet mill to obtain a lithium-rich manganese-based single crystal positive electrode material Li with both fluorine doping and carbon coating modification. 1.2 Ni 0.25 Mn 0.55 O 1.93 F 0.07 @C,D 50 =0.45μm, D 90 =0.60um.
[0081] A positive electrode plate is prepared by coating a slurry made of a lithium-rich manganese-based single crystal positive electrode material that is both fluorine-doped and carbon-coated, a conductive agent, a binder and a solvent.
[0082] A lithium-ion battery comprising the positive electrode sheet and the negative electrode sheet;
[0083] The active material on the negative electrode plate is selected from one or more of graphite, artificial graphite, silicon-carbon material, lithium metal negative electrode and lithium-carbon negative electrode material.
[0084] Comparative Example 2
[0085] The difference from Comparative Example 1 is that the doping amount of PVDF is changed, specifically:
[0086] (4) PVDF dual modification: The doping amount of PVDF is 1.5 mol%, and the amount of lithium source added and the calcination process are the same as those in comparative example 1, to obtain a lithium-rich manganese-based polycrystalline positive electrode material Li with loose secondary particles and both fluorine doping and carbon coating modification. 1.2 Ni 0.25 Mn 0.55 O 1.97 F 0.03 @C.
[0087] (5) Preparation of single crystal: The lithium-rich manganese-based polycrystalline positive electrode material is crushed in a jet mill to obtain a lithium-rich manganese-based single crystal positive electrode material Li with both fluorine doping and carbon coating modification. 1.2 Ni 0.25 Mn 0.55 O 1.97 F 0.03 @C,D 50 =0.40μm, D 90 =0.64um.
[0088] Comparative Example 3
[0089] The difference from Comparative Example 1 is that no crushing is performed at the single crystal stage, and the composition of the obtained single crystal is approximately Li 1.2 Ni 0.2 Mn 0.6 O2-rich lithium manganese-based polycrystalline cathode material, D 50 =2.45μm, D 90 =3.25um.
[0090] Comparative Example 4
[0091] The difference from Comparative Example 1 is that in the PVDF double modification stage, the calcination temperature is changed to 910°C and then kept warm for 13 hours. Specifically:
[0092] (4) PVDF double modification: the pre-oxidized [Ni 0.3125 Mn 0.6875 The precursor of ](OH)2 was mixed with PVDF (HSV900, doping amount was 3.5 mol%) and LiOH·H2O (TM:Li molar ratio = 1:1.55) and heated in nitrogen atmosphere at 3℃min -1 Heat to 500℃ and keep it for 400min, then heat it at 2℃min -1 The temperature was raised to 910℃ and kept for 900min to obtain a lithium-rich manganese-based polycrystalline cathode material Li with loose secondary particles and both fluorine doping and carbon coating modification. 1.2 Ni 0.25 Mn 0.55 O 1.93 F 0.07 @C.
[0093] (5) Preparation of single crystal: The lithium-rich manganese-based polycrystalline positive electrode material is crushed in a jet mill to obtain a lithium-rich manganese-based single crystal positive electrode material Li with both fluorine doping and carbon coating modification. 1.2 Ni 0.25 Mn 0.55 O 1.93 F 0.07 @C.
[0094] Comparative Example 5
[0095] The difference from Comparative Example 1 is that in the PVDF double modification stage, the calcination temperature is changed to 950°C and then kept warm for 13 hours. Specifically:
[0096] (4) PVDF double modification: the pre-oxidized [Ni 0.3125 Mn 0.6875The precursor of ](OH)2 was mixed with PVDF (HSV900, doping amount was 3.5 mol%) and LiOH·H2O (TM:Li molar ratio = 1:1.55) and heated in nitrogen atmosphere at 3℃min -1 Heat to 500℃ and keep it for 400min, then heat it at 2℃min -1 The temperature was raised to 950℃ and kept for 13h to obtain a lithium-rich manganese-based polycrystalline cathode material Li with loose secondary particles and both fluorine doping and carbon coating modification. 1.2 Ni 0.25 Mn 0.55 O 1.93 F 0.07 @C.
[0097] (5) Preparation of single crystal: The lithium-rich manganese-based polycrystalline positive electrode material is crushed in a jet mill to obtain a lithium-rich manganese-based single crystal positive electrode material Li with both fluorine doping and carbon coating modification. 1.2 Ni 0.25 Mn 0.55 O 1.93 F 0.07 @C.
[0098] Comparative Example 6
[0099] The difference from Comparative Example 1 is that in the PVDF double modification stage, the calcination temperature is changed to 930°C and then kept warm for 11 hours. Specifically:
[0100] (4) PVDF double modification: the pre-oxidized [Ni 0.3125 Mn 0.6875 The precursor of ](OH)2 was mixed with PVDF (HSV900, doping amount was 3.5 mol%) and LiOH·H2O (TM:Li molar ratio = 1:1.55) and heated in nitrogen atmosphere at 3℃min -1 Heat to 500℃ and keep it for 400min, then heat it at 2℃min -1 The temperature was raised to 930℃ and kept for 11h to obtain a lithium-rich manganese-based polycrystalline cathode material Li with loose secondary particles and both fluorine doping and carbon coating modification. 1.2 Ni 0.25 Mn 0.55 O 1.93 F 0.07 @C.
[0101] (5) Preparation of single crystal: The lithium-rich manganese-based polycrystalline positive electrode material is crushed in a jet mill to obtain a lithium-rich manganese-based single crystal positive electrode material Li with both fluorine doping and carbon coating modification. 1.2 Ni 0.25 Mn 0.55 O 1.93 F 0.07 @C.
[0102] Comparative Example 7
[0103] The difference from Comparative Example 1 is that in the PVDF double modification stage, the calcination temperature is changed to 930°C and then kept warm for 15 hours. Specifically:
[0104] (4) PVDF double modification: the pre-oxidized [Ni 0.3125 Mn 0.6875 The precursor of ](OH)2 was mixed with PVDF (HSV900, doping amount was 3.5 mol%) and LiOH·H2O (TM:Li molar ratio = 1:1.55) and heated in nitrogen atmosphere at 3℃min -1 Heat to 500℃ and keep it for 400min, then heat it at 2℃min -1 The temperature was raised to 930℃ and kept for 15h to obtain a lithium-rich manganese-based polycrystalline cathode material Li with loose secondary particles and both fluorine doping and carbon coating modification. 1.2 Ni 0.25 Mn 0.55 O 1.93 F 0.07 @C.
[0105] (5) Preparation of single crystal: The lithium-rich manganese-based polycrystalline positive electrode material is crushed in a jet mill to obtain a lithium-rich manganese-based single crystal positive electrode material Li with both fluorine doping and carbon coating modification. 1.2 Ni 0.25 Mn 0.55 O 1.93 F 0.07 @C.
[0106] Comparative Example 8
[0107] The difference from Comparative Example 1 is that oxygen is used for sintering during the PVDF double modification stage, specifically:
[0108] (4) PVDF double modification: the pre-oxidized [Ni 0.3125 Mn 0.6875 The precursor of ](OH)2 was mixed with PVDF (HSV900, doping amount was 3.5 mol%) and LiOH·H2O (TM:Li molar ratio = 1:1.55) and heated in an oxygen atmosphere at 3 °C min -1 Heat to 500℃ and keep it for 400min, then heat it at 2℃min -1 The temperature was raised to 930 ° C and kept for 13 hours to obtain a lithium-rich manganese-based polycrystalline cathode material Li with loose secondary particles and both fluorine doping and carbon coating modification. 1.2 Ni 0.25 Mn 0.55 O 1.93 F 0.07 @C.
[0109] (5) Preparation of single crystal: The lithium-rich manganese-based polycrystalline positive electrode material is crushed in a jet mill to obtain a lithium-rich manganese-based single crystal positive electrode material Li with both fluorine doping and carbon coating modification. 1.2 Ni 0.25 Mn 0.55 O 1.93 F 0.07 @C.
[0110] Comparative Example 9
[0111] The difference from Comparative Example 1 is that the amount of PVDF added is 0%, specifically:
[0112] (4) PVDF double modification: the pre-oxidized [Ni 0.3125 Mn 0.6875 The precursor of ](OH)2 was mixed with LiOH·H2O (TM:Li=1:1.55 molar ratio) and heated in oxygen at 3℃min -1 Heat to 500℃ and keep it for 400min, then heat it at 2℃min -1 The temperature was raised to 930℃ and kept for 13h to obtain the lithium-rich manganese-based polycrystalline cathode material Li 1.2 Ni 0.25 Mn 0.55 O2@C.
[0113] (5) Preparation of single crystal: The lithium-rich manganese-based polycrystalline positive electrode material is crushed in a jet mill to obtain a lithium-rich manganese-based single crystal positive electrode material Li 1.2 Ni 0.25 Mn 0.55 O2@C.
[0114] The lithium-rich manganese-based single crystal positive electrode materials obtained in the above examples and comparative examples were assembled into button batteries. The electrochemical performance test results obtained in the charge and discharge range of 2.3-4.55V are shown in the following table:
[0115]
[0116]
[0117] Through comparative analysis of the data in the table, it can be seen that compared with the unmodified lithium-rich manganese-based single crystal positive electrode material, the initial discharge capacity and cycle capacity retention rate of the lithium-rich manganese-based single crystal positive electrode material after fluorine doping and carbon coating based on PVDF are significantly improved. This result fully demonstrates that the fluorine doping and carbon coating synergistic modification strategy based on PVDF can effectively optimize the electrochemical properties of the material and provide a practical technical path for improving the performance of lithium-rich manganese-based positive electrode materials.
[0118] Depend on Figure 1 It can be seen that the primary particles of the precursor present a typical needle-shaped morphology. At the same time, the bonding between these particles is relatively loose. This structural feature not only provides favorable conditions for the uniform bonding of materials in the subsequent lithiation process, but also helps to form single crystal particles with good crystallinity in the air flow milling process, which is of great significance for optimizing material properties.
[0119] Depend on Figure 2 It can be seen that the single crystal cathode material is discretely distributed as a whole, with an average particle size of around 0.20-0.45 μm. A smaller particle size has a larger specific surface area, providing more reaction sites for the insertion / extraction of lithium ions, thereby significantly improving the charge and discharge capacity of the material. Figure 3 It can be seen that the scanning energy spectrum of the sample modified by fluorine doping and carbon coating based on PVDF shows that C and F elements are evenly distributed on the surface, which indicates that the doping is relatively uniform, which not only helps to optimize the surface structure of the material, enhance the electronic conductivity and ion diffusion rate of the material, but also effectively improve the structural stability and interface compatibility of the material.
[0120] Depend on Figure 4 It can be seen that compared with the unmodified sample, the characteristic peak position and intensity in the XRD spectrum of the sample modified with PVDF are basically consistent, and no obvious impurity peaks appear. This shows that the synergistic modification strategy does not damage the crystal structure of the sample while optimizing the surface properties of the material, and successfully achieves a balance between surface modification and bulk structural stability, providing structural guarantees for maintaining the intrinsic electrochemical properties of the material and further exerting the modification effect.
[0121] Depend on Figure 5 It can be seen that the original single crystal sample exhibits a discharge capacity of 224.64mAh / g and a coulombic efficiency of 77.44%; and the samples modified with PVDF are higher than the unmodified single crystal samples, which shows that the synergistic modification strategy can effectively optimize the electron transport and ion diffusion properties of the material, improve the reversible specific capacity of the material and the energy utilization efficiency during the charge and discharge process, and significantly improve the comprehensive electrochemical performance of lithium-rich manganese-based single crystal cathode materials. Figure 6 It can be seen that after 100 cycles at 0.5C, the capacity retention rate of the PVDF-modified sample is also better than that of the original sample.
[0122] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.
Claims
1. A method for preparing a lithium-rich manganese-based single crystal cathode material by synergistic modification of fluorine doping and carbon coating based on PVDF, characterized in that: The following steps are involved: S1. Solution preparation: Prepare a transition metal salt solution at a molar ratio of Ni:Mn=1:(2.2-3), and simultaneously prepare a NaOH aqueous solution and an NH3·H2O aqueous solution; S2. Precursor preparation: The transition metal salt solution, NaOH aqueous solution and NH3·H2O aqueous solution are slowly pumped into a reactor containing NH3·H2O and deionized water at the same time, and the pH value of the reaction is controlled to be maintained at 11-11.
2. After the reaction is completed, [Ni x Mn y ](OH)2 precursor, wherein 0.25≤x≤0.3125,0.6875≤y≤0.75, the [Ni x Mn y The particle size of the ](OH)2 precursor is 2-5 μm; S3, precursor pre-oxidation: the [Ni x Mn y ](OH)2 precursor is pre-sintered in a pure oxygen atmosphere; S4, the pre-sintered [Ni x Mn y The precursor of ](OH)2 is mixed with PVDF and lithium source, and then calcined twice in nitrogen atmosphere to obtain a lithium-rich manganese-based polycrystalline cathode material Li with loose secondary particles and both fluorine doping and carbon coating modification. 1.2 Ni x Mn y O 2-z F z @C, where 0.20≤x≤0.25,0.55≤y≤0.60,0≤z≤0.1; S5, crushing the lithium-rich manganese-based polycrystalline positive electrode material under a jet mill to obtain a lithium-rich manganese-based single crystal positive electrode material Li with both fluorine doping and carbon coating modification. 1.2 Ni x Mn y O 2-z F z @C.
2. The method for preparing a lithium-rich manganese-based single crystal cathode material by synergistic modification of fluorine doping and carbon coating based on PVDF according to claim 1, characterized in that: Ni in the transition metal salt solution in step S1 2+ and Mn 2+ The total concentration is 2-4 molL -1 ; The concentration of the NaOH aqueous solution is 2-4 mol L -1 The concentration of the NH3·H2O aqueous solution is 1-2 mol L -1 .
3. The method for preparing a lithium-rich manganese-based single crystal cathode material by synergistic modification of fluorine doping and carbon coating based on PVDF according to claim 1, characterized in that: In step S1, the transition metal salt is selected from one of sulfate, chloride and nitrate, and the sulfate is NiSO4·6H2O and MnSO4·H2O.
4. The method for preparing a lithium-rich manganese-based single crystal cathode material by synergistic modification of fluorine doping and carbon coating based on PVDF according to claim 1, characterized in that: During the preparation of the small-particle precursor in step S2, the reaction temperature is controlled at 50-55° C., and stirring is performed continuously in an inert protective gas atmosphere at a stirring rate of 700-900 rpm.
5. The method for preparing a lithium-rich manganese-based single crystal cathode material by synergistic modification of fluorine doping and carbon coating based on PVDF according to claim 1, characterized in that: The pre-sintering temperature in step S3 is 400-500° C. and the time is 300-360 minutes.
6. The method for preparing a lithium-rich manganese-based single crystal cathode material by synergistic modification of fluorine doping and carbon coating based on PVDF according to claim 1, characterized in that: The lithium source in step S4 is selected from at least one of LiOH·H2O, LiNO3, and Li2CO3; the pre-sintered [Ni x Mn y ]The molar ratio of the (OH)2 precursor to the lithium source is 1:(1.50-1.60).
7. The method for preparing a lithium-rich manganese-based single crystal cathode material by synergistic modification of fluorine doping and carbon coating based on PVDF according to claim 1, characterized in that: The secondary calcination in step S4 is specifically as follows: heating to 500-600°C at a heating rate of 2°C / min-5°C / min in an oxygen atmosphere, keeping the temperature for 6-8 hours for sintering; then heating to 910-950°C, keeping the temperature for 10-15 hours for solid phase lithium insertion reaction.
8. The method for preparing a lithium-rich manganese-based single crystal cathode material by synergistic modification of fluorine doping and carbon coating based on PVDF according to claim 1, characterized in that: The added amount of the PVDF is 0-5 mol % based on the amount of the total anionic substances.
9. An application of a PVDF-based fluorine-doped and carbon-coated synergistically modified lithium-rich manganese-based single crystal positive electrode material prepared according to any one of claims 1 to 8, characterized in that: The prepared positive electrode material is combined with a conductive agent, a binder and a solvent to form a slurry to form a positive electrode sheet.
10. The use of a PVDF-based fluorine-doped and carbon-coated synergistically modified lithium-rich manganese-based single crystal positive electrode material according to claim 9, characterized in that: The prepared positive electrode sheet is used for the preparation of lithium-ion batteries, and when preparing lithium-ion batteries, the active material on the negative electrode sheet is selected from one or more of graphite, artificial graphite, silicon-carbon material, lithium metal negative electrode and lithium-carbon negative electrode material.
Citation Information
Cited By
Lithium-rich manganese-based positive electrode material and preparation method and application thereof
CN121020666A
Doped and coated modified lithium-rich manganese-based positive electrode material, preparation method thereof and battery
CN121748337A